IGFBP7-AS1 is a p53-responsive long noncoding RNA downregulated by Epstein-Barr virus that contributes to viral tumorigenesis. (28th December 2021) - Dang, Wei; Cao, Pengfei; Yan, Qijia; Yang, Li; Wang, Yiwei; Yang, Jing; Xin, Shuyu; Zhang, Jing; Li, Jing; Long, Sijing; Zhang, Wentao; Zhang, Senmiao; et al.
Abstract: Epstein-Barr virus (EBV) is closely related to the development of several malignancies, such as B-cell lymphoma (B-CL), by the mechanism through which these malignancies develop remains largely unknown. We previously observed downregulation of the long noncoding RNA (lncRNA) IGFBP7-AS1 in response to EBV infection. However, the role of IGFBP7-AS1 in EBV-associated cancers has not been clarified. Here, we found that expression of IGFBP7-AS1, as well as its sense gene IGFBP7, is decreased in EBV-positive B-CL cells and clinical tissues. IGFBP7-AS1 stabilizes IGFBP7 mRNA by forming a duplex based on their overlapping regions. The tumour suppressor p53 transcriptionally activates IGFBP7-AS1 expression by binding to the promoter region of the lncRNA gene. The IGFBP7-AS1 expression is able to be rescued in EBV-positive cells in wild-type (wt) p53-dependent manner. IGFBP7-AS1 inhibits the proliferation and promotes the apoptosis of B-CL cells. Moreover, tumorigenic properties due to the depletion of IGFBP7-AS1 were restored by exogenous expression of IGFBP7 or wt-p53. Furthermore, the functional p53/IGFBP7-AS1/IGFBP7 axis facilitates apoptosis by suppressing the production and secretion of the NPPB signal peptide and further regulating the cGMP-PKG signalling pathway. This study demonstrates that EBV promotes tumorigenesis, particularly in B-CL progression, by downregulating the novel p53-responsive lncRNA IGFBP7-AS1. Highlights: IGFBP7-AS1 is a p53-responsive lncRNA downregulated by EBV in B-cell lymphoma. IGFBP7-AS1 regulates IGFBP7 expression by stabilizing IGFBP7 mRNA. IGFBP7 reduces the production and secretion of the signal peptide NPPB. IGFBP7 promotes apoptosis via inhibiting NPPB-mediated cGMP/PKG pathway.